Moving to ASP.NET : web development with VB.NET. - Harris, Steve, ....-; MacDonald, Rob, ....- (Berkeley : Apress, 2002)
Samenvatting:Steve Harris and Rob Macdonald have applied their unrivaled .NET exposureand teaching pedigree to make Moving to ASP.NET: Web Development with VB.NET the most comprehensive, yet concise, introduction to ASP.NETdevelopment available.Whereas many .NET books cover only the basics, Moving to ASP.NET leadsthe reader from simple concepts and development tips through to detailedand informative chapters on ASP.NET architecture, advanced design andscalability considerations, and the multifaceted topic of Web security.Special chapters that cover creating mobile Web Applications for use withcell phones, learning XML, and building .NET Web Services ensure that thereader is fully informed, not just about where ASP.NET is being appliedtoday, but also about those areas set to become increasingly important incoming years.The unique structure of Moving to ASP.NET delivers real ASP.NET contentstarting from Chapter 1, while relegating general .NET and Webprogramming concepts to a set of carefully designed appendixes. Harrisand Macdonald bring years of real experience programming and teaching.NET to bear and deliver ASP.NET programming techniques that really work,explained in a way that makes sense.
Keywords: Programmeren; Visual basic (programmeertaal).; Www world wide web